IMPLEMENTATION OF KURIKULUM MERDEKA IN TERMS OF TEACHERS’ ABILITY TO DEVELOP LESSON PLANS - Thana, Paskha Marini; Ramli, Ratu Bulkis (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
The implementation of Kurikulum Merdeka has not yet been fully carried out by schools in the South Papua region. Meanwhile, the government's target is that in the academic year 2024/2025, all schools will have implemented Kurikulum Merdeka. The launch of Kurikulum Merdeka program is a form of effort to recover learning after the Covid-19 pandemic period, where there was a lag in learning at every level of education. As a new program, the implementation of Kurikulum Merdeka requires readiness from schools, especially teachers as curriculum implementers, in designing, implementing, and evaluating learning. This study aims to describe the results of the analysis regarding the implementation of Kurikulum Merdeka that has been carried out for one academic year at SMP Negeri 3 Merauke, specifically focusing on the ability of teachers to develop lesson plans. The subjects of this study are 13 teachers. The research methodology used is qualitative descriptive method with data collection techniques through observation, interviews, questionnaires, and documentation studies. The results of the data analysis show that the ability of teachers to develop lesson plans in implementing Kurikulum Merdeka is classified as fairly good, but there are still some challenges faced by teachers, especially in creating teaching modules.